2021
DOI: 10.3390/smartcities4010022
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Electric Vehicles: Technologies and Challenges

Abstract: Electric Vehicles (EVs) are gaining momentum due to several factors, including the price reduction as well as the climate and environmental awareness. This paper reviews the advances of EVs regarding battery technology trends, charging methods, as well as new research challenges and open opportunities. More specifically, an analysis of the worldwide market situation of EVs and their future prospects is carried out. Given that one of the fundamental aspects in EVs is the battery, the paper presents a thorough r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
400
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 822 publications
(407 citation statements)
references
References 73 publications
0
400
0
7
Order By: Relevance
“…In addition, in a PHEV, the battery can be charged externally. A very recent review that contains data on the different battery sizes, in kWh, for different vehicles can be found in reference [26].…”
Section: Mild Hybrid and Phev Engine Lubricationmentioning
confidence: 99%
“…In addition, in a PHEV, the battery can be charged externally. A very recent review that contains data on the different battery sizes, in kWh, for different vehicles can be found in reference [26].…”
Section: Mild Hybrid and Phev Engine Lubricationmentioning
confidence: 99%
“…In addition, in a PHEV, the battery can be charged externally. (A very recent review that contains data on the different battery sizes, in kWh, for different vehicles can be found in reference [21]).…”
Section: Mild Hybrid and Phev Engine Lubricationmentioning
confidence: 99%
“…The intermittent nature of engine operation can lead to lower engine oil temperatures (compared to that typical of conventional engines). In addition, Fan et al [21] found higher levels of fuel dilution in the lubricant (more details are given in Section 5). They also noted that tailpipe emissions (NOx and PM) could be higher since the aftertreatment systems were not always at optimum operating temperature.…”
Section: Mild Hybrid and Phev Engine Lubricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion of electrical mobility in cities is an investigated topic in many papers, e.g. [14][15][16].…”
Section: Introductionmentioning
confidence: 99%